Multiple Standing Waves for Nonlinear Schrödinger-Poisson Systems - Jian Zhou; Yunshun Wu (Journal of Function Spaces)
In this paper, we consider the following nonlinear Schrödinger-Poisson systems. Under suitable conditions on V, K, g, and h, when 1<s<6, we obtain two nontrivial solutions for the problem and when gx,· is odd and 6<s<∞, we obtain infinitely many solutions for the problem.